Pengaruh Konten Edukasi Neptune TV di Maxstream Terhadap Tingkat Pengetahuan Sektor Bahari Mahasiswa (Survei Kepada Mahasiswa IPB Fakultas Perikanan dan Ilmu Kelautan) - Cristina, Mega Agita (UNIVERSITAS KALBIS, 2023)
One of the new media that is widely used to add insight and knowledge the Maxstream application. Maxstream provides a lot of informative content. Like the Neptune TV content channel. Neptune TV is educational content containing information about marine and fisheries issued by the Ministry of Maritime Affairs and Fisheries.Considering that public knowledge related to the sea currently still relatively low, especially teenagers. The purpose of this research is to find out whether there an influence and how much influence the educational content of Neptune TV on Maxstream has on the level of knowledge of the maritime sector of students. By using the theory of hypodermic theory with a quantitative approach. This study uses a survey method of distributing questionnaires to 202 IPB student respondents. Based on the results of the processed data, correlation coefficient value is 0.878, so can be concluded that there a very strong influence of Neptune TV's educational content on Maxstream on the level of knowledge of IPB students. And the level of knowledge up to the level of understanding.